Relationship Between Invasive Fungal Infection and Hypostatic Pneumonia: A Prospective Cohort Study - Liu, Lin; Liu, Chang; Cai, Jianrong; Chen, Jiayun; Chen, Jie; Fu, Yuanyuan; Yi, Kexin; Wang, Hui; Li, Xue (Frontiers in Microbiology, 2022)
Background The short-term mortality of hypostatic pneumonia (HP) is very high, and the treatment outcome is poor. The clinical diagnosis and treatment are primarily focused on bacterial and viral infection, ignoring the role of fungal infection at present. This study aims to validate the relationship between Invasive Fungal Infections (IFI) and HP. Methods In the cross-sectional study, a total of 11,371 participants have been enrolled. In the prospective cohort study, 4441 individuals have been included at baseline and followed up from 2015-2019 with a total person years of 8484.65. Standard procedures were used to assess questionnaire investigations, laboratory testing and anthropometric indicators. For data analysis, Logistic regression, restricted cubic spline, log-rank regression, Cox regression and linear mixed effects model were applied to assess the relationship between IFI and HP risk longitudinally. Results In the cross-sectional study, elevated BDG concentrations are associated with a higher risk of HP prevalence in the total population, men and women [ORT3 vs T1 (95% CIs): 2.12 (1.55, 2.91); 2.01(1.35, 2.99); 2.34 (1.39, 3.94)], which were verified by a dose-effect relationship in the restricted cubic spline model. In the cohort study, Cox and Log-rank regression showed that elevated BDG concentrations are associated with a significantly higher risk of HP incidence than participants with lower BDG concentrations [HRT3 vs T1 (95%CIs): 2.72 (1.36,5.43), PLog-rank = 0.0086]. During 5 years, the GLB and CRP were always on the top in the highest category of BDG concentrations. Between low and high BDG concentration, the total trend of GLB concentration was falling and the total trend of CRP concentration was rising with the increase of years (all the P-values < 0.0001). Conclusions In this study, IFI is associated with a higher risk of HP, with time sequence and related mechanisms requiring further investigation in the future.